2017
DOI: 10.1186/s12907-017-0044-1
|View full text |Cite
|
Sign up to set email alerts
|

Bone pathologic fracture revealing an unusual association: coexistence of Langerhans cell histiocytosis with Rosai-Dorfman disease

Abstract: BackgroundThe coexistence of Rosai-Dorfman disease (RDD) with Langerhans cell histiocytosis (LCH) is very rare, as to date only 17 cases have been reported in the english literature. The pathophysiology of this uncommon co-occurrence still remains enigmatic and a subject of various speculations.Case presentationWe report a case of a 30-year-old female patient who presented with a pathologic fracture of the left proximal femur. Her medical history was unremarkable, there were no fever, skin lesions, lymphadenop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…14 Alternatively, few studies have shown some 'bank' cells demonstrating features of both RDD and LCH. 9 These bank cells may also explain one condition evolving into another. Our study may represent the same evolution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Alternatively, few studies have shown some 'bank' cells demonstrating features of both RDD and LCH. 9 These bank cells may also explain one condition evolving into another. Our study may represent the same evolution.…”
Section: Discussionmentioning
confidence: 99%
“…10 Orbital RDD and LCH are both rare manifestations of histiocytic disorders. The co-existence of RDD and LCH in a patient has been reported in few studies only, mostly affecting separate organs 8,9,[11][12][13][14] (Table 2). We hereby report a case of co-occurrence of orbital RDD and LCH in a patient with lymphadenopathy and orbital mass.…”
Section: Introductionmentioning
confidence: 99%
“…Langerhans cell histiocytosis (LCH) and RDD coexisting as 2 distinct lesions has been reported, as have LCH and JXG, and RDD and JXG . LCH and RDD coexistence as a single lesion has also been recently reported . O'Malley et al have recently evaluated clonal abnormalities and genetic gains and/or losses in LCH and RDD coexistence, and highlight that these diseases may belong to a spectrum linked by clonal abnormalities .…”
Section: Discussionmentioning
confidence: 99%
“…54,55 Rosai-Dorfman disease and LCH are distinct clinicopathologic entities, but rare cases with concurrence of both conditions in a single site have been described, including cases involving bone and soft tissue, suggesting a possible relationship between the two. [56][57][58] Furthermore, BRAF-V600E mutations have been detected in such combined cases, suggesting that Langerhans cells and RDD histiocytes may derive from a common precursor. 59 One case of nodal RDD with confirmed BRAF-V600E mutation has been reported, representing a promising therapeutic target, especially for patients with refractory or extensive disease.…”
Section: Pathogenesismentioning
confidence: 99%